Beetroot Extract as Fluorescence Probes for Copper Ion Detection in Aqueous Solution - Ganesan Krishnan; Nurul Badrina Aiman Rashidi; Zakirah Buhari (CV Media Inti Teknologi, 2025)
Backgorund of Study: Copper contamination in water poses serious health and environmental risks. Excessive exposure can lead to critical human health issues and is toxic to aquatic organisms. Existing detection techniques are often expensive and complex, highlighting the need for more accessible, eco-friendly alternatives. Aims and Scope of Paper: This study explores betanin from beetroot as a low-cost, eco-friendly fluorescence probe for detecting copper ions, highlighting its sensitivity and potential for environmental and biomedical use. Methods: Beetroot extract was analyzed using UV-Vis, PL, and FTIR spectroscopy to examine changes in betanin’s optical properties in response to different copper ion concentrations. Result: The fluorescence intensity of betanin decreased as copper ion concentration increased. A linear correlation (R² = 0.792) was observed between copper levels and absorbance, and the sensitivity was calculated at –6.21828 × 10⁻⁴ A.U./ppm, demonstrating betanin's strong potential as a copper ion detector. Conclusion: The study confirms betanin from beetroot shows strong potential as a low-cost, eco-friendly copper ion detector, supporting sustainable sensing solutions across various fields.